Prevalence of asthma among teenagers attending school in Tahiti. Issue 2 (June 1988) - Liard, R; Chansin, R; Neukirch, F; Levallois, M; Leproux, P
Abstract : The prevalence of asthma was studied in 6731 adolescents (average age 13.5 years, 48.6% boys) attending school in three towns of the isle of Tahiti, according to the ethnic origin of both parents. The pupils completed a self-administered questionnaire in class; 14.3% gave an affirmative answer to the question "Have you ever had attacks of asthma?" (cumulative prevalence). That prevalence was 11.4% in the Europeans, 13.7% in the Chinese, 13.8% in the Polynesians, 15.3% in those whose parents were "halves" (half-bred from Polynesians and Europeans), and 16.0% in the miscellaneous group (= other origins) (P less than 0.02). Asthma was significantly more frequent in boys only among the Europeans and those with one European parent. The results of this study confirm the high prevalence of asthma in French Polynesia found in a previous study. They give no evidence of a racial difference in prevalence but suggest an influence of environment.